The endosomal transcriptional regulator RNF11 integrates degradation and transport of EGFR - Scharaw, Sandra; Iskar, Murat; Ori, Alessandro; Boncompain, Gaelle; Laketa, Vibor; Poser, Ina; Lundberg, Emma; Perez, Franck; Beck, Martin; Bork, Peer; Pepperkok, Rainer (The journal of cell biology, 2016)
Stimulation of cells with epidermal growth factor (EGF) induces internalization and partial degradation of the EGF receptor (EGFR) by the endo-lysosomal pathway. For continuous cell functioning, EGFR plasma membrane levels are maintained by transporting newly synthesized EGFRs to the cell surface. The regulation of this process is largely unknown. In this study, we find that EGF stimulation specifically increases the transport efficiency of newly synthesized EGFRs from the endoplasmic reticulum to the plasma membrane.
Gesehen am 13.05.2020